Investigating The Effect of Media Supplements on Xylanase Production by Aspergillus versicolor via Solid State Fermentation - Normarjana, Binti Ahmad Darus (Universiti Malaysia Sarawak (UNIMAS), 2017)
The utilization of agricultural waste has become an alternative to produce many types of enzymes. Enzymes are produced through the process of solid-state fermentation (SSF) which offers more advantages compared to submerged fermentation (SmF) including high productivity, extended stability of products and low production costs. In Sarawak, local agro wastes can be found abundantly as it has been reported in 2015, that the industry of agriculture increased 14% from the previous year which contributed to RM14.86 billion to the economy of the country. In this study, to produce xylanase, Aspergillus versicolor was used with pineapple leaves as the substrate. The substrate was supplemented with different media supplements from carbon and nitrogen sources ranging from 0.5% to 2.0% to increase the production of xylanase. Enzyme activity was determined by xylanase assay and analysed using DNS method. Based on the results, it is found that the best media supplement to be used for nitrogen sources was sodium nitrate with the concentration of 1.5%. For carbon sources, sucrose was the best media supplement to be used in producing xylanase at the concentration of 0.5%.